Budaya Sekolah dalam Mendorong Pembinaan Guru : School Culture in Encouraging Teacher Development - Sabariah, Sabariah; Hartono, Hartono; Zairunah, Zairunah; Lian, Lisda (Thawalib: Jurnal Kependidikan Islam, 2024)
School culture is one of the factors influencing school management systems in efforts to improve teacher performance. The research aims to determine and explain school culture in fostering teacher development. This study uses a qualitative phenomenological approach. Data collection techniques were conducted through observation, interviews, and document studies. Data validity was ensured through triangulation of sources, techniques, and prolonged observation. The results of the study indicate: (1) school culture: motivating teachers to work, disciplining teachers through the socialization of school rules and checking teacher attendance, conducting regular meetings among teachers, and building positive communication between the school principal and teachers and among teachers. (2) impacts: improved teacher performance and smooth management of learning activities. Conclusion: school culture has been implemented effectively and systematically. Research implications: serving as input and learning materials for other schools in teacher development.